A Novel Strategy for Scalable High‐Efficiency Planar Perovskite Solar Cells with New Precursors and Cation Displacement Approach. Issue 44 (14th September 2018) - Li, Fengzhu; Zhang, Yu; Jiang, Ke‐Jian; Zhang, Chaoshen; Huang, Jin‐Hua; Wang, Huijia; Fan, Haochen; Wang, Pengcheng; Chen, Yongjie; Zhao, Wenchao; Li, Xiangjun; Yang, Lian‐Ming; et al.
Abstract: Methylammonium iodide (MAI) and lead iodide (PbI2 ) have been extensively employed as precursors for solution‐processed MAPbI3 perovskite solar cells (PSCs). However, the MAPbI3 perovskite films directly deposited from the precursor solutions, usually suffer from poor surface coverage due to uncontrolled nucleation and crystal growth of the perovskite during the film formation, resulting in low photovoltaic conversion efficiency and poor reproducibility. Herein, propylammonium iodide and PbI2 are employed as precursors for solution deposition of propylammonium lead iodide (PAPbI3 ) perovskite film. It is found that the precursors have good film formability, enabling the deposition of a large‐area and homogeneous PAPbI3 perovskite film by a scalable dip‐coating technique. The dip‐coated PAPbI3 film is then subjected to an organic‐cation displacement reaction, resulting in MAPbI3 film with high surface coverage and crystallinity. With the MAPbI3 film as the light absorber, planar PSCs are fabricated, and stabilized power conversion efficiencies of 19.27% and 15.68% can be achieved for the devices with active areas of 0.09 and 5.02 cm 2, respectively. The technology reported here provides a robust and efficient approach to fabricate large‐area and high‐efficiency perovskite cells for practical application. Abstract : A pseudo‐3D CH3 CH2 CH2 NH3 PbI3 perovskite film is deposited by a scalable dip‐coating technique with high surface coverage, and then conversed to a high‐quality 3D CH3 NH3 PbI3 perovskite film via an organic‐cation displacement approach. With the MAPbI3 film as the light absorber, planar perovskite solar cells are fabricated, affording stabilized power conversion efficiencies of 19.27% and 15.68% for 0.09 and 5.02 cm 2 devices, respectively.